LOCAL PERFUME BUSINESS DEVELOPMENT STRATEGY (Case Study on Marvest Fragrance) - Bustamil Ramadhani; Jusni; Muhammad Toaha (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to analyze the internal and external conditions and formulate appropriate business strategies for Marvest Fragrance in facing the challenges of the local perfume market in Makassar City. The analysis is conducted through an internal factor analysis using the marketing mix and STP (Segmenting, Targeting, Positioning), and external factors through PEST analysis (Political, Economic, Social, Technological) and Porter’s Five Forces model. The results of the study indicate that Marvest Fragrance’s internal strengths include highquality products, competitive prices, a professional team, good financial management, production and distribution efficiency, and marketing through social media. On the other hand, its weaknesses include limitations in human resources, capital, product variety, shipping processes, and a narrow market segment. External opportunities include economic and population growth in Makassar, the perfume trend among young people, and government support for SMEs. The external threats faced are inflation, new competitors, shipping costs and delays, as well as high buyer bargaining power and product substitutes. The recommended strategy is to leverage strengths and opportunities (SO) by optimizing social media, expanding the market through efficient financial management, and improving distribution supported by human resources and technology.